ANALISIS PENGARUH EXPERIENTIAL MARKETING, KUALITAS PELAYANAN, DAN FASILITAS TERHADAP KEPUTUSAN MENGINAP KEMBALI MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Pada Pelanggan Hotel @HOM Kudus) - Rina Kurnia; Imroatul Khasanah (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to test and prove that service quality affects customer satisfaction. Data collection from this study involved 105 respondents with the main criteria being 17 years of age and over and having made a decision to stay overnight. The data obtained will then be analyzed using the Structural Equation Model (SEM) with the AMOS version 24 program. Based on this research, it was found that experiential marketing had a negative and insignificant effect on customer satisfaction. In addition, service quality has a positive and significant effect on customer satisfaction. In this study also found facilities have a positive and significant effect on customer satisfaction. Then lastly, customer satisfaction which is the intervening variable has a positive and significant effect on the dependent variable on the decision to stay again. Based on the explanation above, there is 1 rejected hypothesis and 3 accepted hypotheses.